Carbon nanotube–silicon heterojunction solar cells with surface-textured Si and solution-processed carbon nanotube films. Issue 96 (30th September 2016) - Muramoto, Eri; Yamasaki, Yuhei; Wang, Feijiu; Hasegawa, Kei; Matsuda, Kazunari; Noda, Suguru
Abstract : Solution-processed carbon nanotube films fit with textured Si substrates, yielding solar cells with dark surface and improved power conversion efficiency. Abstract : Carbon nanotube (CNT)–silicon (Si) heterojunction solar cells are fabricated with surface-textured Si substrates. Using a dilute alkaline solution, common etchant in the Si solar cell industry, we formed a pyramidal texture on the Si substrate surface. The texture effectively enhances the absorption of the incident light, improving the short-circuit current density by ∼1.3-fold, up to 33.1 mA cm −2 . We fabricated CNT–Si solar cells with a power conversion efficiency (PCE) of 10.4% without any anti-reflective coatings or doping of the CNTs. Moreover, the CNT films were prepared from commercialized CNT agglomerates by a mild solution-based process, which is well suited for the fabrication of CNT–Si solar cells with large area. We also achieved a PCE of 9.57% for a flat cell with careful removal of surfactant from and doping by nitric acid of the CNT films. These findings suggest that with the combination of surface-textured Si and solution-processed CNT films, efficient and low-cost CNT–Si solar cells may be realized.